Detection of meat adulteration in veal sausages using a multiplex PCR technique - Sawicki, Wojciech; Żochowska-Kujawska, Joanna (Biotechnology and Food Science, 2016)
Previous methods used to detect veal contamination by lower value meat lacked easiness and accuracy This study describes a simple procedure for detecting origin of meat in processed meat products. A rapid (5h) protocol based on multiplex PCR was developed to detect undeclared chicken meat (a specific mitochondrial DNA sequence) in Polish veal sausages. Simultaneously a PCR assay was successfully optimized for amplification of 274-bp DNA fragment extracted from meat products using designed species-specific primer pairs for the detection of veal meat. This procedure also enabled differentiation of bovine or/and chicken meat from their less expensive porcine substitute